Psychology, risk, health and deployed military operations. Issue 2 (30th November 2018) - Verrall, Neil
Abstract : This article will focus on a study by the UK Defence Science and Technology Laboratory (Dstl) which investigated the risk propensity and health behaviours of UK army personnel deployed to Iraq in 2007 as part of Op TELIC. The study addressed the concept of impulsive sensation seeking and how this interacted with health behaviours associated with alcohol, smoking, driving and sex at predeployment, during deployment and postdeployment, as well as perceptions of risk and psychological well-being. There is also a description of other deployment-related risk and health research and analysis undertaken by Dstl as part of a wider discussion on the nature of both risk and health on deployed operations.